O ensino de desigualdades e inequações em um curso de Licenciatura em Matemática - Melo, Marcelo de (2007)
The present study aims to detect how pre-service mathematic teachers develop inequalities among their students and what are the sources of their work in this subject. In order to accomplish that, we chose Raymond Duval theoretical framework about semiotic registers of representation. According to this theory the coordination among several semiotic representational registers promote the conceptualization of a mathematical object. In this perspective, we collected and analyzed data from: institutional documents; interviews with four teachers of the investigated course; didactical materials recommended and used by them. Besides that, we used data from student s exercise books